2005
DOI: 10.1159/000089163
|View full text |Cite
|
Sign up to set email alerts
|

One Cycle of Bleomycin, Etoposide and Cisplatin plus Two Cycles of Etopeside and Cisplatin Chemotherapy in Selected Patients with Low-Volume Stage II Nonseminomatous Germ Cell Tumor of the Testis

Abstract: Objective: To assess the feasibility of bleomycin omission from second and third cycles of bleomycin, etoposide and cisplatin (BEP) chemotherapy in low-volume stage II nonseminomatous germ cell tumor patients who achieve a normal tumor marker level after the first cycle of treatment. Materials and Methods: Out of 59 nonseminomatous testicular cancer patients with low-volume retroperitoneal disease, serum markers normalized after the first cycle of treatment in 30 cases. 12 patients completed 3BEP (group 1; yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…In low-volume stage II NSGCT patients one cycle of BEP plus two cycles of EP was as effective as three cycles of BEP. 12 However, a recent study of men diagnosed with stage I NSGCT reported that adjuvant chemotherapy was significantly more effective in preventing recurrences than an RPLND 13 Although not statistically significant, there was a suggestion that men treated in hospitals with a residency training program were more likely to receive chemotherapy than men treated in hospitals with our such training programs. The observation that chemotherapy use varies by geographic region suggests that physicians have differing opinions on the value of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In low-volume stage II NSGCT patients one cycle of BEP plus two cycles of EP was as effective as three cycles of BEP. 12 However, a recent study of men diagnosed with stage I NSGCT reported that adjuvant chemotherapy was significantly more effective in preventing recurrences than an RPLND 13 Although not statistically significant, there was a suggestion that men treated in hospitals with a residency training program were more likely to receive chemotherapy than men treated in hospitals with our such training programs. The observation that chemotherapy use varies by geographic region suggests that physicians have differing opinions on the value of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patient atteint d'une tumeur germinale non-sé minomateuse de stade avancé Premiè re ligne de traitement : chimiothé rapie L'analyse a porté sur un essai randomisé de non-infé riorité de qualité mé thodologique correcte comparant chez 270 patients 4E 500 P à 3BE 500 P [14], une é tude ré trospective de qualité mé thodologique critiquable comparant chez 30 patients les toxicité s entre (1 BEP + 2 EP) et 3 BEP [34] et trois cohortes ré trospectives de qualité mé thodologique critiquable [28][29][30] incluant respectivement 87 patients traité s par (RPLND + 2 EP), 389 patients recevant 4 EP et 62 patients traité s selon les protocoles SWENOTECA.…”
Section: Curage Ganglionnaireunclassified
“…Ré sultats en termes de balance bé né fice/risque globalement cohé -rents : protocole Culine et al [14] (ndp B1), Mezvrishvili et Managadze [34] (ndp D) ou Kondagunta et al [29,30] (ndp C). À noter que les patients de bon pronostic IGCCC ont une moins bonne tolé rance avec 4E 500 P que 3BE 500 P (neutropénies de grades 3-4, p = 0,0002) bien que les taux de dé cè s ne soient pas statistiquement diffé -rents, l'augmentation observé e, difficilement acceptable dans cette situation de maladie volontiers curable, pose des questions.…”
Section: Curage Ganglionnaireunclassified